Utilization SiCw and Al2O3 Particles on Aluminum Matrix in Improving Strength and Hardness Composite Materials - Suarsana, I Ketut; Santhiarsa, I.G. Ngurah (Journal of Materials Engineering and Processing Technology, 2017)
Utilization reinforcement fiber-based composite material and particles in the manufacture of composite materials now have potential to be developed and researched. Various sources of fiber and reinforcement in particle form can be obtained from natural fibers from plants and fiber that has been subjected to a previous treatment. Indonesia has the potential of natural resources is of particular importance as a source of fiber from plants is also in the form of metallic aluminum (bauxite) from fossils.. This material can be used for the needs of the industry as the manufacture of composite base Aluminum and as a reinforcement in the form of fibers or particles of alumina. The method of making Aluminum Matrix Composites (AMC) with a powder metallurgy process at the compression force / compaction 2.5 tons using a hydraulic press equipment, holding time 15 minutes, and the treatment process in the variation of the composition by weight (%wt). Variations in the composition of the fiber reinforcement Silicon Carbon (SiC) and Al 2 O 3 (alumina) on a matrix Aluminum is: 30% SiC + 0% Al 2 0 3 , 27% SiC + 3% Al 2 0 3 , 24% SiC + 6% Al 2 0 3 and 21% SiC + 9% Al 2 0 3 with a matrix of 70% Al, on condition tempertaure 500 o C, 550 o C and 600 o C. After the composite material is formed, tested for mechanical properties due to the influence of variations in composition between matrix and reinforcement in composites. Characteristics test performed in the laboratory to knowing strength and hardness properties of composite materials. Furthermore sought the relationship between the nature of each composition fiber reinforcement and a Al 2 O 3 forming SiC composites made to know the benefits of reinforcing fibers and particles of alumina. Keywords : Al 2 O 3 , hardness, SiCw and strength.